Tidal dynamics on the upper continental slope of the eastern Gulf of Cádiz: The interplay between water masses and its effects on seafloor morphology. (March 2023) - Roque, D.; Gomiz-Pascual, J.J.; Bruno, M.; Sánchez-Leal, R.; González, C.J.; García, M.; Fernández-Salas, L.M.; Hernández-Molina, F.J.
Highlights: The influence of tides on the seafloor morphology of the eastern Gulf of Cádiz. Water masses close to the near-critical strips would favor the generation of internal waves. Oceanographic processes interact at different times and spatial scales determining the morphology. Knowledge of bottom currents and their modulation is needed for understanding sea-floor morphology. Abstract: Although the effects of tidal dynamics have been studied in shallow marine environments and morphologically restricted straits, the impact of these processes on deep-water marine environments remains to be studied in depth. This study highlights the influence of tides on the seafloor morphology of the eastern Gulf of Cádiz, near the exit of the Strait of Gibraltar. Two moorings, one with an Acoustic Doppler current profiler (ACDP) and another one with a thermistor chain, and local and regional profiles of salinity, temperature, and ADCP reveal the water mass distribution in the study area and associated oceanographic processes. The intermediate water masses flowing along the continental slope are the Eastern North Atlantic Central Water (ENACW) and the Mediterranean Outflow Water (MOW), bound by an interface located regionally at depths greater than 300 m, but identified locally at much shallower depths (up to 150 m) in the studied upper slope. The hydrodynamics of the area are governed by barotropic tidal currents, the MOW upper core, and the internal tides, which act at different time and spatial scales shaping the local terraced sea-floor morphology and determining the dominant sedimentary processes. The obtained results allow a better understanding of how secondary oceanographic processes are modulating the water mass circulation in this particular hot spot and their importance in explaining the formation and evolution of morphological depositional and erosional features.